Green HRM and employee efficiency: The mediating role of employee motivation in emerging small businesses - Khan, Ali Junaid; Ul Hameed, Waseem; Iqbal, Jawad; Shah, Ashfaq Ahmad; Tariq, Muhammad Atiq Ur Rehman; Bashir, Furrukh (Frontiers in Environmental Science, 2022)
The modern organization structure expects that the human resource department should train the employees effectively to sustain the environment. This study aims to understand the role of Green Human Resource Management (GHRM) in the efficiency of the organization's employees in small and medium enterprises (SMEs) of Pakistan. The questionnaire was developed on a five-point Likert scale to collect primary data from the target respondents, and the target respondents of this study were the employees of SMEs in Pakistan. The results of the study indicate that GHRM is an important tool to motivate and train employees, which ultimately increases the efficiency of employees. This study demonstrates that the SMEs in Pakistan need to consider the critical role of GHRM as it is emerging and provides reliable resources as per the organization's requirements for better performance. This study contains the future recommendation for the studies to consider and contribute in the literature as well as to the practices of SMEs in Pakistan for the efficiency of their employees.